Simulation-based scheduling system at R2 Print Enterprise Kuantan - Atikah, Selamat (2016)
This thesis deals with decision support tool for dynamic job shop scheduling at R2 Print Enterprise, Kuantan. The objective of this thesis is to understand the job shop production in dynamic environment, to develop scheduling system based on real-time data and to implement it in R2 Print Enterprise. The thesis describes the scheduling techniques with aim to delivering jobs on time and can adapt to the rush orders. Here, a printing company with two different jobs are modelled in Arena Simulation Software to study the suitable scheduling heuristic rules to be implemented to the problems. The main heuristic rules studied in this thesis are First In First Out (FIFO), Earliest Due Date (EDD), Shortest Processing Time (SPT) and Longest Processing Time (LPT). The performance measures taken in this research are the Total Average Time Delays, Total Average Product Delays, Total Product Flow Times and the Resource Utilizations. The Large Format Product (LFP) job considered n = 6 products and m = 4 work centers (6x4) while the Paper Product (PP) job considered n = 7 products and m = 3 work centers (7x3). The product sequence and processing time are dependent on each other. The sequence length can vary from three to four operations and there is no flexibility on the sequence. The model is run for 5 days with 9 hours operation time per day. The obtained results indicate that in LFP job, there is no single rule which dominates the others although EDD seems to be more effective than other rules.The summarized results show that the best scheduling rules for Total Time Delays is SPT, for Total Product Delays is EDD, for Total Flow Times is EDD the best scheduling rules for Resource Utilization is SPT. In PP job, there is also no dominant single rule that clearly dominant although the most successing rules are those with short processing times. The summarized results indicate that the best scheduling rules for Total Time Delays is EDD. For Total Product Delays are FIFO and EDD, for Total Flow Times is SPT and for Resource Utilization, the best scheduling rule is SPT, FIFO, LPT and EDD as they give equal results. The results can significantly reduce the time to produce and reduce the delay in delivering jobs.